Pemberdayaan Kelompok Tani Maju Terhadap Petani Jagung Di Desa Belinteng Kecamatan Sei Bingai Kabupaten Langkat - Timura, Rezi Ardafi Maulana; Lubis, Mitra Musika (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2025)
Many social problems have occurred in our beloved country, including poverty. This is a social problem that we must face through joint planning; if not considered and not handled properly, it will hurt the community’s economy, both now and in the future. With this problem, the community can create a way to survive later without considering the negative impacts that can arise or be caused to themselves or those around them. In Belinteng village, Sei Bingai sub-district, Langkat district, there are several farmer group organizations where the farmer groups join and work together to improve the economy. In Belinteng village, there is a problem that exists, namely, that there is no role for farmer groups in the village, so that if a problem arises, the farmers immediately notify the extension worker. Farmer organizations play an important role in the development of the agricultural sector in Indonesia, which is one of the media for solving farmers' problems. In addition, farmer organizations can ensure that farmers unite and work together for the good of fellow farmers and not vice versa, to bring each other down and look weak in front of large companies and modern markets. This study also aims to analyze the level of empowerment of corn farmers through farmer groups and the problems face. How is the level of empowerment of corn farmers through farmer groups in Belinteng village, Sei Bingai sub-district, Langkat district, North Sumatra province? The research method in the journal used in this study is qualitative and quantitative data, while the data sources used are secondary data and primary data.